Contextualizing Satyagraha within the Feminist Movement in the US. Issue 2 (December 2016) - Sharma, Ayesha
The author argues that the mainstream US feminist historical documentation framework—the feminist waves—have organized feminist history to primarily record historical events that involve high status women (i.e white middle-class cisgender women). This paper dissects the feminist waves to suggest that their key events and actors represent the centering of a socially privileged group. The author analyzes the framework to understand the ways in which the waves may encourage this privileging—largely through the erasure and exclusion of the personal and political truths of the most vulnerable feminists and their satyagraha against intertwining inequalities at the grassroots.